Reading as Dialogue: About the Creative Dialogue Tasks at Literature Lessons in the 7 th Grade - S O Shebalkova (Peoples' Friendship University of Russia (RUDN University), 2013)
The theme of this article is the compliance of the existing model of reading to the requirements of the FGOS OOO (FSES CGE) standard. The promising model of reading, which supposes an interactive dialogue between the author and the reader and the topical questions of the teaching of literature and psychology of reading are also discussed in this article. The author describes a system of dialogue tasks in literature classes in the 7th grade and gives the most successful student's work as an example of educational feedback in the system "author-reader".